MULTIMEDIA REPRESENTATION OF KNOWLEDGE IN ACADEMIC DISCOURSE - Tomskaya, Maria; Zaytseva, Irina (Verbum, 2018)
The article focuses on academic presentations created with the help of multimedia programmes. The presentation is regarded as a special form of new academic knowledge representation. An academic presentation is explored as a multimodal phenomenon due to the fact that different channels or modes are activated during its perception. Data perception constitutes a part of the context which in itself is a semiotic event involving various components (an addresser, an addressee, the message itself, the channel of communication and the code). The choice of the code and the channel depends on different factors (type of the audience, the nature of the message, etc). In this way, the information for non-professionals will be most likely presented through visualization with the help of infographics (schemes, figures, charts, etc). Talking about the professional audience the speaker may resort to visualization to a lesser degree or he may not use it at all. His message will be transmitted only with the help of verbal means, which will not prevent the audience from perceiving and understanding new knowledge correctly. The presentation regime of rapid successive slide show may be regarded the heritage of ‘clip thinking’ which is characterized by a non-linear, simultaneous way of information perception. At the present stage of technology development visualization is becoming the most common means of transmitting information in academic discourse, due to peculiarities of data perception by the man of today.
Keywords: academic presentation; multimodal text; visualization; infographics; ‘clip thinking’